Positive feedbacks between phosphorus deposition and forest canopy trapping, evidence from Southern Mexico. Issue 4 (22nd November 2013) - Runyan, Christiane W.; D'Odorico, Paolo; Vandecar, Karen L.; Das, Rishiraj; Schmook, Birgit; Lawrence, Deborah
Abstract [1] For some phosphorus (P)‐limited ecosystems, vegetation can be sustained by atmospheric P inputs. The ability of the canopy to trap airborne particles influences atmospheric P deposition. This dependence suggests a positive feedback, which could impact forest regeneration following deforestation. We examine how the amount of P deposited atmospherically varies as a function of forest canopy characteristics. We quantify the amount of P in bulk deposition (i.e., rainfall and dry deposition) and throughfall from a mature forest and 6 year old successional vegetation stand. To rule out the possibility that P enrichment in throughfall is due to canopy leaching, we construct an artificial forest made of P‐free plastic materials. We then compare throughfall samples collected beneath the artificial forest with those collected beneath the successional vegetation due to similarities in forest characteristics such as height and stem density. Over 1 year, 0.6 ± 0.1 kg P ha−1 yr−1 were deposited in the open area, 0.8 ± 0.0 kg P ha−1 yr−1 beneath the successional vegetation, 0.5 ± 0.0 kg P ha−1 yr−1 beneath the artificial forest, and 1.9 ± 0.0 kg P ha−1 yr−1 beneath the mature forest. Results also showed an enrichment of P concentration beneath the artificial forest relative to the open area. Atmospheric P sources sustain 37% of the annual P demand in the mature forest, but only 13% in the successional vegetation. Thus, following deforestation, more of the P demand would have to be met from other sources that if unavailable, could lead to conditions where the forest does not recover.